INSTITUTIONAL INVESTORS AND FIRM INNOVATION: A TEST OF COMPETING HYPOTHESES - KOCHHAR, RAHUL; David, Parthiban (Strategic Management Journal, 1996)
There is much debate about the effect of institutional investors on firm innovation. This paper tests three competing hypotheses by including differences among institutions in their ability to influence firms. Results using an outcome-based measure of innovation indicate that institutions do not foster short-term orientation; instead they may influence firms to increase innovation.